Acute Protective Effects of Simvastatin in the Rat Model of Renal Ischemia-Reperfusion Injury: It Is Never Too Late for the Pretreatment - Zoran Todorović; Zorica Nešić; Radan Stojanović; Gordana Basta-Jovanović; Sanja Radojević-Škodrić; Ružca Veličković; Prabal K. Chatterjee; Christoph Thiemermann; Milica Prostran (Journal of Pharmacological Sciences, 2008)
Acute pretreatment with a single i.v. bolus injection of simvastatin (1 mg/kg) significantly protects rat kidney injured by ischemia-reperfusion (I/R) (45 min + 6 h). We aimed to determine the optimal timing of such a pretreatment. The effects of both injections of simvastatin before ischemia and reperfusion were similar regarding total histological score. However, simvastatin injected 30 min before ischemia was 30% – 75% more effective in reduction of serum creatinine levels and interstitial edema score, while its injections 5 and 30 min before reperfusion were 25% – 60% more effective in reduction of tubular necrosis score and fractional excretion of Na+. However, the observed differences do not seem to offer significant advantage in clinical settings. Keywords:: simvastatin, acute pretreatment, ischemia-reperfusion (I/R) renal injury